Survival and Prognostic Factors in Patients with Hepatocellular Carcinoma Treated by Percutaneous Ethanol Injection: A 10-Year Experience - Roberto Mazzanti; Umberto Arena; Pietro Pantaleo; Lorenzo Antonuzzo; Greta Cipriani; Bruno Neri; Clara Giordano; Fabio Lanini; Serena Marchetti; Paolo Gentilini (Canadian Journal of Gastroenterology)
The treatment of early and intermediate stage hepatocellular carcinoma (HCC) is still debated. Surgical treatments are considered to be the only curative procedures available, and only for a minority of patients. Percutaneous ethanol injection (PEI) is an established technique for the ablation of HCC nodules, and shows survival rates similar to those of resection. The efficacy of PEI in patients with biopsy-proven viral cirrhosis and small to intermediate inoperable HCC was evaluated. One hundred twenty-seven patients (85 men, 42 women, mean age 63 years, range 51 to 92 years, 115 hepatitis C virus-positive, 12 hepatitis B virus-positive) were enrolled between January 1993 and December 2002. They all underwent a standard PEI procedure and were prospectively followed-up. Overall median survival rate was 28 months (range six to 112 months). The following parameters were associated with a significantly longer survival: nodule diameter smaller than 30 mm (P=0.0480), the presence of a perinodular boundary (P=0.0008), serum alpha-fetoprotein less than 20 ng/mL (P=0.0104), a Child-Pugh A class score (PÃ0.0001) or a Cancer of the Liver Italian Program score of 0 (PÃ0.0001) and the presence or absence of small esophageal varices (P=0.013). The 19 patients with all these favourable characteristics showed an overall median survival of 61 months. An alpha-fetoprotein below 20 ng/mL was associated with significantly longer disease-free survival (P=0.0009). The Child-Pugh and Cancer of the Liver Italian Program scores were effective in predicting prognosis of these patients. In conclusion, PEI still represents a safe and economically sound treatment for HCC.